Pengaruh Penempatan Blade Turbin Propeller Di Tengah Blade Turbin Venturi Terhadap Performa Turbin Hybrid - Agustinus Agustinus; Iwan Kurniawan (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
Wind turbines are windmills that are used to generate electricity. The basic principle works, namely converting the mechanical energy from the wind into rotational energy, then the rotation of the mill is used to rotate the generator, which in turn will generate electricity. Over time, many turbine innovations have been used. Innovation can be done by fixing existing deficiencies or adding new things so that these products have additional functions. In this research, innovations were carried out in wind turbines. That is, two different types of turbines are combined into one, namely a combination of a conventional turbine (propeller) and a wind ball energy (venturi) turbine. This innovation is made so that the hybrid turbine can work and function at low wind speeds. This research is intended to determine the performance of this hybrid turbine by placing the propeller blade in the middle of the venturi turbine blade and varying the ratio of the length of the turbine propeller blade to the diameter of the venturi turbine. So that the right size and maximum results are obtained in the manufacture of this hybrid turbine. Key words: Hybrid Turbine, Propeller Turbine, Venturi Turbine.